Functional analysis of colonic bacterial metabolism: relevant to health? - Hamer, Henrike M. (American Physiological Society, 2012)
With the use of molecular techniques, numerous studies have evaluated the composition of the intestinal microbiota in health and disease. However, it is of major interest to supplement this with a functional analysis of the microbiota. In this review, the different approaches that have been used to characterize microbial metabolites, yielding information on the functional end products of microbial metabolism, have been summarized. To analyze colonic microbial metabolites, the most conventional way is by application of a hypothesis-driven targeted approach, through quantification of selected metabolites from carbohydrate (e.g., short-chain fatty acids) and protein fermentation (e.g., p-cresol, phenol, ammonia, or H(2)S), secondary bile acids, or colonic enzymes. The application of stable isotope-labeled substrates can provide an elegant solution to study these metabolic pathways in vivo. On the other hand, a top-down approach can be followed by applying metabolite fingerprinting techniques based on (1)H-NMR or mass spectrometric analysis. Quantification of known metabolites and characterization of metabolite patterns in urine, breath, plasma, and fecal samples can reveal new pathways and give insight into physiological regulatory processes of the colonic microbiota. In addition, specific metabolic profiles can function as a diagnostic tool for the identification of several gastrointestinal diseases, such as ulcerative colitis and Crohn's disease. Nevertheless, future research will have to evaluate the relevance of associations between metabolites and different disease states.